THE RESPONSIBILITY OF ENTREPRENEURS IN MANAGING INVESTMENTS TO ENSURE BUSINESS SUSTAINABILITY: A CONCEPTUAL AND PRACTICAL REVIEW - H. Deni Salahuddin; Gunawan Widjaja (Review of International Economy and Finance, 2025)
This study discusses the responsibility of entrepreneurs in managing investments as an effort to ensure business continuity through conceptual and practical reviews. A literature review approach was used to collect and analyse literature related to the concept of entrepreneurial responsibility in investment management, including stewardship theory, corporate social responsibility (CSR), and corporate governance principles. In addition, responsible investment management practices in the real business world are also examined, including diversification strategies, risk management, integration of ESG (Environmental, Social, and Governance) principles, and the use of digital technology to improve the effectiveness of investment management. The results of the study indicate that entrepreneurs who are able to manage investments responsibly can not only maintain business sustainability but also create social and environmental added value. This study provides recommendations for entrepreneurs and policymakers to place greater emphasis on ethics, transparency, and adaptation to market dynamics in investment management so that businesses remain competitive and sustainable.